Displaced: Life in the Katrina Diaspora - Weber, Lynn; Peek, Lori (The Katrina Bookshelf, 2012)
Hurricane Katrina forced the largest and most abrupt displacement in U.S. history. About 1.5 million people evacuated from the Gulf Coast preceding Katrina’s landfall. New Orleans, a city of 500,000, was nearly emptied of life after the hurricane and flooding. Katrina survivors eventually scattered across all fifty states, and tens of thousands still remain displaced. Some are desperate to return to the Gulf Coast but cannot find the means. Others have chosen to make their homes elsewhere. Still others found a way to return home but were unable to stay due to the limited availability of social services, educational opportunities, health care options, and affordable housing. The contributors to Displaced have been following the lives of Katrina evacuees since 2005. In this illuminating book, they offer the first comprehensive analysis of the experiences of the displaced. Drawing on research in thirteen communities in seven states across the country, the contributors describe the struggles that evacuees have faced in securing life-sustaining resources and rebuilding their lives. They also recount the impact that the displaced have had on communities that initially welcomed them and then later experienced “Katrina fatigue" as the ongoing needs of evacuees strained local resources. Displaced reveals that Katrina took a particularly heavy toll on households headed by low-income African American women who lost the support provided by local networks of family and friends. It also shows the resilience and resourcefulness of Katrina evacuees who have built new networks and partnered with community organizations and religious institutions to create new lives in the diaspora.